1997
DOI: 10.1038/bjc.1997.260
|View full text |Cite
|
Sign up to set email alerts
|

Squamoid features and expression of involucrin in primary breast carcinoma associated with high histological grade, tumour cell necrosis and recurrence sites

Abstract: Summary Although breast carcinomas are considered to originate from glandular epithelial cells, some exhibit 'squamoid features', comprising stratification with a gradient in the nuclear-cytoplasmic ratio within individual cancer cell nests on microscopy. In parallel with a histological review of squamoid features, we immunohistochemically investigated the expression of involucrin, a marker of terminal squamous differentiation, in 223 breast carcinomas with one to three regional nodal metastases but no distant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…10 CACs and matrix-producing carcinoma (MPC) are morphologically similar, but their similarity and differences with respect to radiology and cytopathology have been reported. [11][12][13] Recent advances in the techniques of biomarker profi ling have led to reports of breast cancers showing squamoid features with involucrin (INV) positivity, 14 myoepithelial differentiation, 9,15 epithelial-mesenchymal transition, 16,17 basal-like phenotypes (as defi ned by gene expression profi ling and immunohistochemical studies [18][19][20], or "stem cell-like" features. 21 Some studies have reported that MBCs express myoepithelial markers 22,23 and are basal-like tumors.…”
Section: Introductionmentioning
confidence: 99%
“…10 CACs and matrix-producing carcinoma (MPC) are morphologically similar, but their similarity and differences with respect to radiology and cytopathology have been reported. [11][12][13] Recent advances in the techniques of biomarker profi ling have led to reports of breast cancers showing squamoid features with involucrin (INV) positivity, 14 myoepithelial differentiation, 9,15 epithelial-mesenchymal transition, 16,17 basal-like phenotypes (as defi ned by gene expression profi ling and immunohistochemical studies [18][19][20], or "stem cell-like" features. 21 Some studies have reported that MBCs express myoepithelial markers 22,23 and are basal-like tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that factors such as S-phase fraction less than 5% [7], expression of parathyroid hormone-related peptide [9], bone sialoprotein [10], and calcium-sensing receptor [11], lack of squamoid differentiation and involucrin expression [12], strand growth pattern, and presence of fibrotic foci in invasive ductal carcinoma [13] are also associated with bone metastasis. In addition, Smid et al [14] have recently identified a 69-gene panel that is relevant to bone metastasis, and many of the genes seem to be involved in the fibroblast growth factor receptor signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…1), 5) fibrotic focus (FF) 7) (absent or present) (Figs. 2 and 3), 6) tumor necrosis (absent or present), 7) extra-mammary fat invasion (absent or present), 8) squamoid character 5) (absent or present) and 9) vascular invasion (absent or present). Since the size and number of FF differs from case to case, histological examination of the entire tissue was necessary to determine the presence of FF.…”
Section: Casesmentioning
confidence: 99%
“…In contrast, tumors with squamoid character and involucrin expression have a low incidence of BM. 5) Tumor metastases to the bone are classified into osteolytic and osteoblastic types. In the former, destruction of the lamellar bone is a typical finding, whereas the latter shows new bone formation within the foci of lamellar bone destruction.…”
mentioning
confidence: 99%